Video games a medium that demands our attention - Bowman, Nicholas David (Electronic media research series, 2018)
"This entry in the BEA Electronic Media Research Series, born out of the April 2017 BEA Research Symposium, takes a look at video games, outlining the characteristics of the medium as cognitive, emotional, physical, and social demanding technologies, and introduces readers to current research on video games. The diverse array of contributors in this volume offer bleeding-edge perspectives on both current and emerging scholarship. The chapters here contain radical approaches that add to the literature on electronic media studies generally and video game studies specifically. By taking such a forward-looking approach, this volume aims to collect foundational writings for the future of gaming studies"...